Biological properties of lemongrass: An overview - Olorunnisola, S.K.; Asiyanbi, H. T.; Hammed, Ademola Monsur; Simsek, Senay (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The use of herbal preparations remained the main approach of folk medicine to the treatment of ailments and debilitating diseases. Initial intensive researches conducted on Lemongrass extracts (tea) may have showed conflicting evidences, however the resurgence in claims of folk medicine practitioners necessitated further inquiry into the efficacy of the tea. Lemongrass tea contains several biocompounds in its decoction, infusion and essential oil extracts. Anti-oxidant, anti-inflammatory, anti-bacterial, anti-obesity, antinociceptive, anxiolytic and antihypertensive evidences of lemongrass tea were clearly elucidated to support initial pharmacological claims. Lemongrass tea was non-toxic, non-mutagenic and receives wide acceptance among alternative medicine practitioners in several developing countries. This review therefore presents previous research activities, technologies and information surrounding bioactivities of lemongrass tea. Areas of future researches which may elucidate mechanisms of the biological properties of lemongrass extracts were highlighted.